Cocrystal and its Application in the Field of Active Pharmaceutical Ingredients and Food Ingredients - Wang, Na; Xie, Chuang; Lu, Haijiao; Guo, Nannan; Lou, Yajing; Su, Weiyi; Hao, Hongxun (Current Pharmaceutical Design, 2018)
Background: The development of solid drug dosage form and food ingredients is constrained by their low solubility, low dissolution, low bioavailability and poor physicochemical properties. Formation of cocrystal is a novel and promising method to enhance and improve the properties of materials without breaking the covalent bonds. Methods: The goal of this review is to summarize the cocrystals and their applications in the field of Active Pharmaceutical Ingredients (APIs) and food ingredients (AFIs), mainly on the effective improvements of APIs' and AFIs' pharmacokinetic, physicochemical and mechanical properties by the formation of cocrystals. Results: After years of research and development on cocrystals in the area of pharmaceutical and food industries, significant progress has been made. Formation of cocrystal is an efficient method for improving the solubility, dissolution rate, permeability and in vivo bioavailability of APIs and AFIs, as well as for enhancing stability and mechanical properties. Conclusion: Cocrystals exhibit complex structures which can conspicuously affect the physical and chemical properties of original substance, with good clinical performance and outstanding stability during processing and storage.
Keywords: bioavailability